An Analysis of the Effectiveness of Emergency Distance Learning under COVID-19 - Son, N.T. (Association for Computing Machinery, 2020)
In this paper, we describe the emergency distance teaching at FPT University in Vietnam to deal with emergency social isolation orders due to the outbreak of the COVID-19 virus. There are many theories as well as guidelines for implementing distance learning in recent years. However, applying them in a short time is not easy, for many factors even impossible such as revise the curriculum, prepare materials, train lecturers and students, prepare the related infrastructure. Therefore, we make many customizations to adapt to the current situation as well as reuse the most available resources. Emergency distance learning is an effective way to deal with diseases. However, exploring its affections to overcome in further phases is necessary. In this study, we analyze the student feedbacks and student achievements after one semester of emergence distance learning. The results show some information about the impact of emergency changes in teaching and examining methods on students. Â© 2020 ACM.